The future of Islam - Esposito, John L. (Oxford University Press, 2010)
A Georgetown University professor and well-known scholar of Islam, Esposito analyzes the current and future practice of Islam in this short but insightful volume. He surveys a number of topics, including identity issues for Muslims living in the West. Esposito highlights the world views of modern Muslim thinkers, such as Tariq Ramadan (Esposito modestly omits mention of his mentorship of some of these scholars). He tackles head-on the myth of Muslim tolerance of 9/11 by pointing to polls showing that the vast majority of Muslims disapproved of the attack and that 358 Muslim employees at the World Trade Center were among the dead. As a senior scientist for Gallup, Esposito has at his command the results of numerous polls of and about Muslims. In this book, he goes beyond the numbers to showcase what Muslims really stand for and want in today's world. Esposito's enthusiasm for his topic makes his book an easy and enlightening read.